INTEGRATION OF GERMAN WITH TECHNICAL SCIENCES - Bukhorova Makhliyo Khojievna (Western European Studies, 2025)
This article covers the theoretical and practical foundations of the integration of the German language with technical sciences. It is emphasized that in the current era of globalization, the importance of knowledge of a foreign language, in particular German, is increasing in the fields of technology and engineering. The possibilities of deep mastery of technical terminology through the German language, independent work with scientific sources, and participation in international cooperation were analyzed. Also, the advantages of combining science and language through the CLIL (content and language integration) method, its role in the development of scientific thinking and professional competence of students are highlighted. The article also presents practical proposals for increasing the effectiveness of the integrated education system
Keywords: German language; technical sciences; integration